A comparative study of physicochemical and antioxidant properties integrated with chemometrics on enzymatic hydrolysates of selected fruit seeds - Hew, Peir Shinn; Wong, Zhian Joe; Wong, Min Feung; Ng, Wen Jie; Ee, Kah Yaw (Springer, 2024)
Fruit seed is one of the by-products of fruit processing that is currently underexploited. In this study, the crude water extracts of guava, longan, and rockmelon seeds were hydrolyzed using enzymes bromelain and alcalase. Their yields (2.47–57.02), TPC (15.53–127.99 mg GAE/g), TFC (18.03–115.15 mg QE/g), protein (14.04–178.60 mg/g), and peptide (23.55–203.97 mg/g) contents were reported. Among the guava seed samples, bromelain hydrolysate (G2) had the highest FRAP (121.489 mg Fe(II)/g), ABTS (IC50 1.713 mg/mL) and DPPH (IC50 0.158 mg/mL) values. Similarly, bromelain hydrolysate of rockmelon seed (R2) exhibited higher FRAP (41.511 mg Fe(II)/g) and ABTS (IC50 2.605 mg/mL) values than the crude extract. However, longan seed crude extract (L1) exhibited higher antioxidant activity than its hydrolysates. Furthermore, chemometric analysis revealed multifaceted relationship among physicochemical and antioxidant parameters, in which L1, bromelain (L2) and alcalase hydrolysates (L3) of longan seed, guava seed crude extract (G1), and G2 associated positively with TPC, TFC, and reducing antioxidant power. Overall, longan and guava seed extracts (L1, G1) and hydrolysates (L2, L3, G2) can be potentially used as antioxidant ingredients for food product development.